Related Relations between kinematic variables and free landing Corner with Air movements skillfully rear airbag horizontal bar in gymnastics - Abdul Slam Abdul Razzaq, Zinah; Mahohammed Sayah, Qasim (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to verify the relationship between the variables of the kinematics liberation corner turn-on device where the players need to corner of gymnastics free occasion so they can complete successfully axle and landing correctly. This study chose 11 players who participated in the 2018 Iraq club championship that was held in Baghdad and analyzed the best performance in the competition. The camera used for (Sony HDR-200 frequency 60 Mbps) after turning photography picture Register to Kinovea program (8.25) for the purpose of extracting the digital data and then treated statistically using the correlation coefficient and decadence pace using the statistical program Spss 19). Liberalization has been the appointment of an independent variable angle of kinematic variables belonging to verify the difference of each factor. The level of significance was set at p <.05.The study concluded that the estimation of the angular velocity and time to be the best worker aviation angle of freedom through 0.320 corner speed and 0.49 flight time and affected significantly on the corner of freedom the importance of less than 0.05 (t = -2.85 -2.92 corner speed and flight time) So we can expect that the center of gravity of the body through the angle of the freedom of the player and axle gymnastics completes successfully and drops the player properly to upgrade its performance in a horizontal bar and remove the danger during the landing. We have consolidated the variables of the angular velocity and time of flight through the results of inputs from 9 variables belonging to explain the angle of freedom. The estimated equations regression line represents the relationship between the corner of speed and release corner flying time. The corner of release = 4.85 x 102.09 corner speed. The corner of release = 177.3 degrees in 74.2x flying time.